2013
DOI: 10.1016/j.bone.2013.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic impact of low amplitude high frequency whole body vibrations on the osteogenesis imperfecta mouse bone

Abstract: Osteogenesis imperfecta (OI) is characterized by extremely brittle bone. Currently, bisphosphonate drugs allow a decrease of fracture by inhibiting bone resorption and increasing bone mass but with possible long term side effects. Whole body mechanical vibrations (WBV) treatment may offer a promising route to stimulate bone formation in OI patients as it has exhibited health benefits on both muscle and bone mass in human and animal models. The present study has investigated the effects of WBV (45 Hz, 0.3 g, 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 56 publications
3
52
1
Order By: Relevance
“…In contrast to other studies, we used LMHFV locally on the calvarial area, while the usual protocol in the earlier experiments was to subject the animal to whole body LMHFV [20, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other studies, we used LMHFV locally on the calvarial area, while the usual protocol in the earlier experiments was to subject the animal to whole body LMHFV [20, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…Animal studies demonstrated LMMS efficacy in growing bones, resulting in gains in trabecular bone volume fraction and cortical area. (11-13) Furthermore, LMMS preserved trabecular bone structure in rats treated with glucocorticoids. (14) …”
Section: Introductionmentioning
confidence: 99%
“…Because RANKL inhibitors have a shorter half-life in bone than do bisphosphonates, they are being investigated as an alternative therapy. Because of the reproducible number of fractures in the oim/oim mouse, this mouse has also been used by others to study the effect of whole-body vibration [37] and gene therapy [31] in preclinical models.…”
Section: Introductionmentioning
confidence: 99%